The Bidding Process of The Cebu Provincial Government: A Case Study - Gabiana, Kyll Deither E.; Polinar, Mark Anthony N.; Baquero, Grace Caroline H. (Future Science / FSH-PH Publications, 2023)
The government can choose the best and most qualified suppliers or contractors through the bidding process, getting the most value for the money spent by the taxpayers. It encourages government procurement to be effective, efficient, and accountable while ensuring the public receives the most for their money. However, the bidding process, particularly in the government, has gotten negative perceptions from the public. For this reason, this case study wanted to explore the bidding process conducted by the Bids and Awards Committee and their perceived constraints as they reflect on the whole process. Also, adjusting schemes made by the officers to the perceived constraints was discussed. Six (6) key informants were selected by the researchers and interviewed individually. As the study employed Creswell’s method, three themes arose that serve the perceived constraints of the officers: (1) Uninterested Buyers, (2) Unqualified Bidders, and (3) the Availability of Signatory. On top of the themes, all key informants indicated that the Cebu Provincial Government’s bidding process followed RA 9184, known as “The Government Procurement Reform Act.” The researchers drew the conclusion that the Provincial Government should take action to ease these constraints by establishing a transformation program focused on improving the bidding process, notably in vetting the bidders' credentials and required paperwork in advance. As part of the program, the organization should embrace cutting-edge practices like digital project approval as the signatory is preoccupied with other crucial tasks.